Endoscopic transoral resection of lingual thyroid - Ruggeri, Carlos Santiago Ruggeri; Acosta, Lautaro; Bedini, Ivo (Revista del Hospital Italiano de Buenos Aires, 2019)
The presence of ectopic thyroid tissue at the base of the tongue is very rare, and most patients have hypothyroidism. The indication of treatment depends on the presence or not of symptoms, surgery being the first choice. Various surgical techniques have been described, being for us the transoral approach with endoscopes the best option, due to the good exposure, and minimum morbidity that it produces. The clinical case of a woman who consulted for odynophagia, with a diagnosis of lingual thyroid and who was successfully treated by a transoral approach with endoscopic assistance is described
Keywords: lingual thyroid; transoral; endoscopic surgery